Injectable Lipid-Based Depot Formulations: Where Do We Stand? - Lisa Rahnfeld; Paola Luciani (MDPI AG, 2020)
The remarkable number of new molecular entities approved per year as parenteral drugs, such as biologics and complex active pharmaceutical ingredients, calls for innovative and tunable drug delivery systems. Besides making these classes of drugs available in the body, injectable depot formulations offer the unique advantage in the parenteral world of reducing the number of required injections, thus increasing effectiveness as well as patient compliance. To date, a plethora of excipients has been proposed to formulate depot systems, and among those, lipids stand out due to their unique biocompatibility properties and safety profile. Looking at the several long-acting drug delivery systems based on lipids designed so far, a legitimate question may arise: How far away are we from an ideal depot formulation? Here, we review sustained release lipid-based platforms developed in the last 5 years, namely oil-based solutions, liposomal systems, in situ forming systems, solid particles, and implants, and we critically discuss the requirements for an ideal depot formulation with respect to the used excipients, biocompatibility, and the challenges presented by the manufacturing process. Finally, we delve into lights and shadows originating from the current setups of in vitro release assays developed with the aim of assessing the translational potential of depot injectables.